Effects of (desgly - arg) vasopressin on cognitive processes in alcoholic patients - Koršić, Mirko (Array, 1991)
The effect of intranasally administered (DesGly9-Arg8) vasopressin (DGAVP) on certain aspects of cognitive functions of alcoholic patients was studied. The investigation was carried out in 103 chronic alcoholic patients. None of the patients suffered from Korsakoff's syndrome, portal encephalopathy or brain damage of other etiology. The trial was double-blind, placebo controlled. Psychological testing, which included certain aspects of attention, short-term and long-term memory and spatial orientation, was carried out on the day before (baseline measurements), on the last day (II), and seven days after the last administration of DGAVP (III). No treatment effect of DGAVP was observed. The results show that investigations with humans are infinitely more complex than those with animals, since a number of physiological and socio-psychological factors must be controlled. In this study of alcoholics two such factors: 1) duration of abstinence and 2) adaptation to test situation were identified.